2011
DOI: 10.1177/0273475311420240
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Scholarship in Marketing Education

Abstract: The teaching environment in business schools has changed dramatically over the last decade. But the last comprehensive review of the scholarship of teaching was conducted more than a decade ago. Where and from whom do the best practices for teaching originate today? To answer this question, the authors examine marketing education scholarship between 2000 and 2009 by assessing individual and institutional productivity in the two primary marketing education journals, Journal of Marketing Education and Marketing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…Three papers that assess educational research productivity in their business-related field are Abernethy and Padgett [2], Lo and Wong [13] and Chan and Thapa [5]. Abernethy and Padgett [2] investigated institutional and individual productivity in the Journal of Marketing Education and Marketing Education Review.…”
Section: Research Productivity In Business Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Three papers that assess educational research productivity in their business-related field are Abernethy and Padgett [2], Lo and Wong [13] and Chan and Thapa [5]. Abernethy and Padgett [2] investigated institutional and individual productivity in the Journal of Marketing Education and Marketing Education Review.…”
Section: Research Productivity In Business Educationmentioning
confidence: 99%
“…Abernethy and Padgett [2] investigated institutional and individual productivity in the Journal of Marketing Education and Marketing Education Review. The authors concluded that "schools with doctoral education orientation or who place the highest emphasis solely on academic research are unlikely to be among the elite institutions in marketing education research".…”
Section: Research Productivity In Business Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many changes have been introduced into marketing education recently (Abernathy and Padgett 2011), and more change may be necessary before marketing programs at colleges and universities are producing the type of graduate who is ready to enter an increasingly competitive workplace (Finch, Nadeau, and O'Reilly 2013;Rosa 2012). In fact, colleges and universities are under significant pressure by stakeholders to provide affordable, sustainable approaches that will prepare students with the skills they need after graduation to achieve success in the workplaces of this new century (Beckem and Watkins 2012).…”
mentioning
confidence: 99%
“…Marketing students need more exposure to marketing metrics (e.g., Saber and Foster 2011), sales education and training (e.g., Cummins et al 2013), technology (e.g., Neilson 2009), and multiculturalism (e.g., Rosa 2012). In addition, much of the marketing curriculum had been designed to equip students with strong communication skills, flexibility, decisiveness, professional skills, and professionalism, by providing more active learning elements in the marketing classroom (Glaser-Segura et al 2010;Peltier, Scovotti, and Pointer 2008), especially experiential methods (Abernathy and Padgett 2011).…”
mentioning
confidence: 99%